(untitled) (ACME, 2023)
The aim of this paper is to examine two bronze Lares found in the excavations of Veleia and kept in the local Antiquarium. The two statuettes have some iconographic peculiarities: one seems to belong to a rare type of Compitales with rhyton and kantharos; the other, iconographically close to the Lar Famliaris, has the attributes placed in a reverse position. In this study I try to contextualize it in the Cisalpine small bronzes tradition, and to deepen the knowledge about these two rare iconographies.